Bee Viruses: Routes of Infection in Hymenoptera - Yañez, Orlando; Piot, Niels; Dalmon, Anne; de Miranda, Joachim R.; Chantawannakul, Panuwan; Panziera, Delphine; Amiri, Esmaeil; Smagghe, Guy; Schroeder, Declan; Chejanovsky, Nor (Frontiers in Microbiology, 2020)
Numerous studies have recently reported on the discovery of bee viruses in different arthropod species and their possible transmission routes, vastly increasing our understanding of these viruses and their distribution. Here, we review the current literature on the recent advances in understanding the transmission of viruses, both on the presence of bee viruses in Apis and non-Apis bee species and on the discovery of previously unknown bee viruses. The natural transmission of bee viruses will be discussed among different bee species and other insects. Finally, the research potential of in vivo (host organisms) and in vitro (cell lines) serial passages of bee viruses is discussed, from the perspective of the host-virus landscape changes and potential transmission routes for emerging bee virus infections.